2005
DOI: 10.1890/03-0569
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Patches and Runoff–erosion as Interacting Ecohydrological Processes in Semiarid Landscapes

Abstract: Ecological and hydrological processes can interact strongly in landscapes, yet these processes are often studied separately. One particularly important interaction between these processes in patchy semiarid lands is how vegetation patches serve to obstruct runoff and then how this retained water increases patch growth that, in turn, provides feedbacks to the system. Such ecohydrological interactions have been mostly demonstrated for semiarid landscapes with distinctly banded vegetation patterns. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
647
2
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 731 publications
(675 citation statements)
references
References 43 publications
14
647
2
12
Order By: Relevance
“…Thus, results support previous research finding that woody encroachment in drylands can result in a major change in ecosystem structure [Bai et al, 2009;Bird et al, 2002;Havstad et al, 2006;Schlesinger et al, 1990], characterized by an increased heterogeneity of vegetation and SOC distribution [Puttock et al, 2013]. Reduction in vegetation cover following woody encroachment decreases vegetative protection of the soil [Ludwig et al, 2005] and increases connectivity [Mayor et al, 2008;Wainwright et al, 2011], leading to accentuated water erosion fluxes [Parsons et al, 1996;Wilcox et al, 2003a]. Greater variation in SOC contents at the woody sites (Table 2) supports the theory that the alteration of hydrological functions associated with woody encroachment results in the occurrence of positive feedback mechanisms [Peters and Herrick, 2001] reinforcing the heterogeneous woody landscape structure into islands of fertility [Schlesinger et al, 1990].…”
Section: Change In Soil C Dynamics Over Vegetation Transitionssupporting
confidence: 89%
“…Thus, results support previous research finding that woody encroachment in drylands can result in a major change in ecosystem structure [Bai et al, 2009;Bird et al, 2002;Havstad et al, 2006;Schlesinger et al, 1990], characterized by an increased heterogeneity of vegetation and SOC distribution [Puttock et al, 2013]. Reduction in vegetation cover following woody encroachment decreases vegetative protection of the soil [Ludwig et al, 2005] and increases connectivity [Mayor et al, 2008;Wainwright et al, 2011], leading to accentuated water erosion fluxes [Parsons et al, 1996;Wilcox et al, 2003a]. Greater variation in SOC contents at the woody sites (Table 2) supports the theory that the alteration of hydrological functions associated with woody encroachment results in the occurrence of positive feedback mechanisms [Peters and Herrick, 2001] reinforcing the heterogeneous woody landscape structure into islands of fertility [Schlesinger et al, 1990].…”
Section: Change In Soil C Dynamics Over Vegetation Transitionssupporting
confidence: 89%
“…Much of this research has addressed the effects of vegetation on fluvial and eolian processes (Wainwright, 2009). Many studies have shown how individuals or stands of shrubs promote run-on, infiltration, and sediment trapping (e.g., Rostagno, 1989;Dunkerly and Brown, 1995;Neave and Abrahams, 2001;Hupy, 2004, and see review by Ludwig et al, 2005). Likewise, bioturbation by small and mediumsized mammals influences hydrological and eolian processes through burrowing activity, creating heterogeneous landscape structure.…”
Section: Introductionmentioning
confidence: 99%
“…One particularly important interaction between these processes in patchy semiarid lands is how vegetation patches serve to control water erosion and then how this retained water runoff and soil material increase vegetation growth that, in turn, provides feedbacks to the system (Ludwig et al, 2005). These interactions could also lead to microtopography change that could further affect water runoff and soil loss processes (Bergkamp, 1998).…”
Section: Introductionmentioning
confidence: 99%